(a-b)[(a+b)3-2ab(a2-b2)]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 18:11:41
(a-b)[(a+b)3-2ab(a2-b2)](a-b)[(a+b)3-2ab(a2-b2)](a-b)[(a+b)3-2ab(a2-b2)](a-b)[(a+b)3-2ab(a2-b2)]=(a&
(a-b)[(a+b)3-2ab(a2-b2)]
(a-b)[(a+b)3-2ab(a2-b2)]
(a-b)[(a+b)3-2ab(a2-b2)]
(a-b)[(a+b)3-2ab(a2-b2)]
=(a²-b²)[(a+b)²-2ab]
=(a²-b²)(a²+b²)
=a^4-b^4
(a-b)[(a+b)3-2ab(a2-b2)]
a-b a2 - b2 3b 1- ----- 除 ---------- + -------a-2b a2 - 4ab + 4b a+b....a-b a2 - b2 3b 1- ----- 除 ---------- + -------a-2b a2 - 4ab + 4b a+b
3a2+ab-2b2=0,求a/b-b/a-(a2+b2)/ab (a,b不等于0)
a2-3a-ab+3b因式分解
计算:a2-2ab/-ab+b2÷(a2/a-b÷2ab/2b-a)
已知A=a2-2ab+b2,B=a2-3ab-b2,求2A-3B
.已知A=a2-2ab+b2,B=a2+2ab+b2,求:2a-3b
已知3a2+ab-2b2=0,求代数式a/b-b/a-(a2+b2)/ab的值
当3a2+ab-2b2=0时,求a/b-b/a-a2+b2/ab的值
2a-3b/b2-a2 -a+3b/a2-b2 +a+2b/a2-b2
2a-3b/b2-a2 -a+3b/a2-b2 +a+2b/a2-b2
已知(a-1)-(a2-b)=-3,求a2+b2-2ab的值a2=a的二次方
如果实数a,b满足a2+2ab+b2=12,a2-b2=4根号3,求a-b/b,a2是a的平方
化简2a2-b2+ab-2ab-2a+b
已知b/a=-3 求a2-2ab-3b平方 /a2-3ab-4b2
化简:[a-b/(a2+ab)]×[(ab-a2)/a2b2-a4]
已知a2+2ab+b2=0,求代数式a(9b-a)+(a+3b)(a-3b)
化简:(a2-b2)/(a2+2ab+b2)÷(2a-2b)/(a+b)